An actin-nucleating activity in polymorphonuclear leukocytes is modulated by chemotactic peptides (The Rockefeller University Press, 1986)
We examined the actin-nucleating activity in polymorphonuclear leukocyte lysates prepared at various times after chemotactic peptide addition. The actin nucleation increases two- to threefold within 15 s after peptide addition, decays to basal levels within 90 s, and is largely independent of cytoplasmic calcium fluxes. The peptide-induced nucleation sites behave as free barbed ends and therefore may increase the level of polymerized actin in vivo. The new nucleation sites may also determine the cellular sites of actin polymerization. This localization of actin polymerization could be important for the directional extension of lamellipodia during chemotaxis.